(3GdfLe GdhgGL aj TQM GdefgGLs - (3eMeO Hf ehSi Hf YjSi GdOejQj GdTGaYj , ceGd GdOjf CHh GdHbGA,J (B808 (3g` s ((3Ydi Hf YWjI GdedbH GdgjJi GdMehi s)
(3ChdgG (B:s
(3cJGH GdUjGe gh ai GddZI GdEeSGc s
(3BNQgG (B:s
(3Je GdcJGH GdKGfi ef GdfLe GdhgGL ai TQM GdefgGL s
(3GdcJGH GdeTQhM(B: (3efgGL GdWGdHjf ddfhhis
(3GdfSNI HgG MhGTs
(3QGLY HbjI GdCLRGA (B-(3heYdheGJ GdfSN(B- (3aj GdfSN(B: 79 (3chjJ h (B80 (3chjJ HLRFjgeGs
(3ai BNQ GdfSNI aGFOI ddTjN TeS GdOjf GdHdGWjfi ai GdCeGfGJ GdTQYjI ai hQbI hGMOI s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
Keywords: (3Gdabg GdTGaYjs